A study on awareness of advertising male breast cancer in Malaysia / Nornatasya Farina Jasman - Jasman, Nornatasya Farina (2019)
Male breast cancer is not a new disease in Malaysia but people still not educate on this issues. They just only know it happen among women not to men. The study cases are choice based on the observation to the lacking of knowledge about male breast cancer among society. Most of the advertising just only approach by giving awareness among the female not in generally. This is happen because they are think just only women can affected from producing milk. Indeed, the information gathered were prove that the breast cancer is causes by poor habits, lifestyle individually, environment and genetics factor. This study is attempt to look into the breast cancer awareness among Malaysian male through the questionnaire districted to male respondent, it is forward that the majority is unaware of the breast cancer. On the research study the researcher using the quantitative as the method approach to get the information by collecting data. The quantitative is based on the observation of awareness breast cancer among male. The research believe by awareness campaign will be able to separate information about the cancer to the public.